Effect of the initial concentration metal ion and adsorbent dose on heavy metal removal using napier grass - Siti Nor Hidayah Mohamad Nor (2024)
In recent decades, the release of heavy metals into aquatic ecosystems has raised concerns in Malaysia. These pollutants primarily enter water bodies due to various industrial activities, which gained momentum with the initiation of a developmental plan. The identified pollutants encompass lead, chromium, mercury, uranium, selenium, zinc, arsenic, cadmium, gold, silver, copper, and nickel. These hazardous substances can originate from mining operations, ore refining, sludge disposal, incinerator fly ash, processing of radioactive materials, metal plating, and the manufacturing of electrical equipment, paints, alloys, batteries, pesticides, or preservatives. Over the past few decades, various methods have been developed for the treatment and removal of heavy metals include adsorption methods. Extensive research has been conducted to remove heavy metals from industrial wastewater using adsorbents produced from agricultural waste, often known as biosorbents. These bio-sorbents have proved safety and biodegradability, making them appropriate for the treatment of heavy metal-contaminated wastewater. Furthermore, Napier grass is a low-cost bio-sorbent capable of removing copper or lead from wastewater. Napier grass, which is mostly composed of cellulose, pectin, and lignin, is good at binding copper and lead ions, allowing them to be separated from wastewater. The biosorption of lead(Pb) from dilute aqueous solution using Napier grass as the biosorbent has been studied. The biosorption study was carried out as a function of initial metal ion concentration, and adsorbent dose. The residual Pb in solution were determined using atomic absorption spectrophotometer (AAS). The synthesized biosorbents were characterized by surface area analyzer. Effects of initial concentration heavy metal ion, and adsorbent dosage on the Pb(II) removal process had been optimized. The study on initial metal ion concentration showed that the biosorption was initial concentration dependent as maximum biosorption of Pb was obtained in the range 5-7 ppm. The biosorption was also adsorbent dose dependent as maximum biosorption was obtained within 0.5g-1.5g of the biosorbent. For the metal ions, the biosorption efficiency increased with increase in initial metal ion concentration.